Faktor Faktor Yang Mempengaruhi Investasi Asing Langsung di Indonesia - Sunarto wage (JURNAL AKUNTANSI BARELANG, 2020)
This study analyzes and analyzes the factors that influence investors to make investments. Many factors influence investors to make direct investments. Researchers are motivated to study and analyze the factors that influence the decision of multinational companies to make direct investments in Indonesia. Based on previous theory and research, there are some of the biggest determinants of investment, labor, infrastructure, trade openness, exchange rates, trade, interest rates, and economic growth. The theoretical basis used in this study of foreign investment is; (1) classical investment theory, (2) Keynesian investment theory, (3) comparative advantage theory, (4) product cycle theory developed, (4) modern monopolistic advantage theory, (5) leader following theory, (6) investment theory cross, (7) financial factor theory, (8) and eclectic theory. The object of research was carried out in Indonesia. To answer the research problem, the data used from 1997 to 2017 in Indonesia are sourced from the 2018 ASEAN Statistics Yearbook and answer using multiple regression with SPSS 25. Based on the research results, market size affects foreign direct investment in Indonesia while the workforce, infrastructure trade openness, exchange rates, ethnicity, and economic growth do not affect direct investment in Indonesia.